Scaffolding Articulation: Fostering Deeper Understanding of Genetic Mutation in Grade 10 Biology - Sacedon, Analie; Bellen, Joy; Managbanag, Camille; Truya, Lorieza; Sarabia, Vian; Suhitado, Adelyn Mae; Verano, Beauty (Journal of Interdisciplinary Perspectives, 2025)
Genetic mutation is a foundational yet complex topic in Grade 10 biology, often posing challenges for learners to articulate clearly due to unfamiliar terminology and abstract processes. This action research was conducted in a public secondary school biology class, utilizing a scaffolded teaching approach to develop learners’ articulation ability in the context of genetic mutation. Strategies included scaffolded questioning, structured peer teaching, and learner progress checklists. The data sources included daily written evaluations, classroom observations, and recorded learner discussions. Results indicated only modest improvements in learners’ written assessments, with mean class-level proficiency scores of 74% on the first day, 76% on the second day, and 79% on the third day, suggesting a limited impact on formal testing outcomes. However, the qualitative findings told a richer story: learners demonstrated growing confidence in explaining genetic mutations, an increasing use of scientific vocabulary, and greater participation in collaborative discussions. Thematic analysis revealed progress in organizing ideas and articulating complex biological concepts during class activities. These findings suggest that scaffolding is most effective as a tool for fostering conceptual articulation, rather than a strategy for formal test preparation. The study underscores that for action researchers and practitioners, capturing the evolving voice of learners through qualitative methods is crucial for understanding the actual impact of an intervention.